PENGARUH INDONESIA: PENGARUH KUALITAS PELAYANAN, FASILITAS PAKET IBADAH UMRAH TERHADAP TINGKAT KEPUASAN JEMAAH PT AMANAH TRAVEL INDONESIA PROVINSI SUMBAR - adelismasari; Zulhelmi (Jurnal Manajemen, 2024)
Service is one of the priorities given by companies, especially companies operating in the service sector. This is a special attraction for the congregation so that they can feel satisfaction with the services provided by the service provider company. The facility factor is no less important, the congregation chooses the best facilities to use, therefore facilities must be a concern. The management of the service provider must make every effort to develop and carry out various strategic steps in an effort to achieve congregational satisfaction. The aim of the research is to find out how the influence of the Umrah Worship Package Facility Service Quality Variable on the level of Congregation Satisfaction at PT Amanah Travel Indonesia, West Sumatra Province. The research used was a research instrument, namely a questionnaire (Likter Scale) with a research sample of 74 respondents. The data analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and R2 Test. The method used is the Quantitative Method. The results of the research conducted show that the Service Quality Variable and the Umrah Worship Package Facilities Variable partially have a significant influence on the level of Congregation Satisfaction at PT Amanah Travel Indonesia Area, West Sumatra Province. And the Simultaneous Test also had a significant influence on the level of Congregation Satisfaction of PT Amanah Travel Indonesia, West Sumatra Province.